Development and evaluation of a real‐time polymerase chain reaction assay for the rapid detection of Talaromyces marneffei MP1 gene in human plasma. Issue 12 (25th July 2016) - Hien, Ha Thuc Ai; Thanh, Tran Tan; Thu, Nguyen Thi Mai; Nguyen, Ashley; Thanh, Nguyen Tat; Lan, Nguyen Phu Huong; Simmons, Cameron; Shikuma, Cecilia; Chau, Nguyen Van Vinh; Thwaites, Guy; Le, Thuy
Summary: Penicilliosis caused by Talaromyces marneffei is a common AIDS‐defining illness in South and Southeast Asia. Diagnosis is based on culture which can take up to 14 days for identification, leading to treatment delay and increased mortality. We developed a TaqMan real‐time PCR assay targeting the MP1 gene encoding an abundant cell wall protein specific to T. marneffei . The assay's performance was evaluated in MP1 ‐containing plasmids, clinical isolates, and plasma from HIV‐infected patients with and without penicilliosis. The assay consistently detected 10 copies of MP1 ‐containing plasmids per reaction and 100 T. marneffei yeast cells per millilitre plasma. There were no amplification with seven other Penicillium species and six other HIV‐associated fungal pathogens tested. The assay was evaluated in 70 patients with AIDS: 50 patients with culture‐confirmed penicilliosis and 20 patients with opportunistic infections other than penicilliosis. The diagnostic sensitivity was 70.4% (19/27, 95% CI: 51.5–84.1%) and 52.2% (12/23, 95% CI: 33.0–70.8%) in plasma samples collected prior to and within 48 h of antifungal therapy respectively. The diagnostic specificity was 100% (20/20, 95% CI: 83.9–100%). This assay provides a useful tool for the rapid diagnosis of T. marneffei infection and has the potential to improve the management of patients with penicilliosis.